Generalised anhidrosis: different lesion sites demonstrated by microneurography and skin biopsy. Issue 4 (16th March 2005) - Donadio, V; Montagna, P; Nolano, M; Cortelli, P; Misciali, C; Pierangeli, G; Provitera, V; Casano, A; Baruzzi, A; Liguori, R
Abstract : Generalised anhidrosis (GA) shows a uniform clinical picture whether the pathogenesis involves intrinsic abnormalities of sweat glands or postganglionic sympathetic cholinergic nerve dysfunction. We describe two patients who presented intolerance to heat and anhidrosis. In the first patient, symptoms started at 33 years of age, and were associated with absent tendon reflexes and a mydriatic right pupil unreactive to light. The other patient had been unable to sweat since birth. GA was diagnosed on the basis of clinical findings and thermoregulatory tests. Microneurography and morphological analysis of the skin and its innervation disclosed a different lesion site underlying GA in the two patients, and distinguished between a postganglionic autonomic nerve fibre lesion and sweat gland dysfunction.